QDMlab: A MATLAB toolbox for analyzing quantum diamond microscope (QDM) magnetic field maps. (October 2022) - Volk, Michael W.R.; Fu, Roger R.; Trubko, Raisa; Kehayias, Pauli; Glenn, David R.; Lima, Eduardo A.
Abstract: Paleomagnetic measurements of rock magnetizations are typically performed using classical net moment rock magnetometers on bulk, millimeter- to centimeter-sized samples. In this case, the limited spatial resolution effectively averages across the signal of multiple populations of magnetic grains, each of which may have a distinct geological history. Magnetic field imaging with the quantum diamond microscope (QDM) allows for the measurement of weakly magnetic (10 −16 Am 2 ) samples at micrometer spatial resolution, potentially isolating the signal of magnetic grain populations and resolving ambiguities from bulk sample analyses. To achieve such high resolution, the QDM retrieves the energy spectrum of nitrogen–vacancy (NV) color centers within micrometer-scale pixels across a millimeter-scale field of view. Therefore, large amounts of data need to be processed to generate a magnetic field map, which itself often requires further specialized analysis. Until now, no freely-available, comprehensive, open-source software package existed that was able to process this type of data. Here we give an overview of the most important features of QDM l a b, our open-source MATLAB toolbox for generating and analyzing QDM magnetic field maps of geologic samples. QDM l a b utilizes modern computational techniques like graphics processing unit (GPU) and spectral fitting routines as well as automated image alignment algorithms. QDM l a b contains easy-to-use functions for (1) generating magnetic field maps from raw QDM data, (2) map editing, and (3) quantifying the net magnetic moment and rock magnetic properties of rock and mineral samples. Highlights: Open source MATLAB toolbox for quantum diamond microscope data. Calculate, correct, edit, and align magnetic field maps. Novel net-moment, and complex map analysis methods.